Geo-authentic Tibetan medicine: a traditional pharmacological resource for promoting human health and wellness - Ning Wang; Hongkang Zhu (Frontiers Media S.A., 2024)
Traditional Tibetan medicine (TTM) is an ancient healing system that has been practiced for more than 2,000 years and involves the use of various medicinal plants for preventing and treating acute mountain sickness, depression, asthma, etc. Geo-authentic medicinal materials, also known as "Daodi herbs" in Chinese, have heightened efficacy and quality relative to their counterparts sourced from alternative geographic locales. In 2024, eight medicinal materials, typified by Cordyceps sinensis Sacc., were listed as geo-authentic Tibetan medicine under the administration of the local government. However, there is no comprehensive review on these geo-authentic TTMs, especially with respect to their pharmacological benefits to human health. This review aims to document the pharmacological properties, phytochemical components, safety, toxicity, and future developments of the geo-authentic TTMs that play essential roles in promoting health and wellness. Plant-derived molecules (i.e., polysaccharides, flavonoids, glycosides, terpenoids, and alkaloids) in the TTMs show therapeutic potentials for the management of both mental and physical health. Finally, the applications and prospects of TTM plants are discussed to support the use of these species in folk medicine for human wellness and to promote public health in modern societies.